VERFICATION OF PROCESS DESIGN OF AN EXTENDED AERATION FOR AL-SHURQAT WASTEWATER TREATMENT PLANT - Saiwan Shamkhi, Mohammed (Journal of Engineering and Sustainable Development, 2016)
The aim of this paper is to verify the treatment process design of Shourqat wastewater treatment plant (WWTP), taking into account the high yearly average temperature that occurs in Iraqi territory. An experimental observed yield (Yobs) has been detected in the laboratory and verified at different temperatures by application of GPS-X model. This paper described the equations of the process design for WWTP. Sludge age (θc) has been correlated to the observed yield (Yobs) and to the mixed liquor suspended solid (MLSS) showing that a valid correspondence has been found between the θc calculate by dividing the total biomass present in the oxidation basin by the total biomass wasted and the θc calculated with taking into account Y, MLSS and BOD removed. An experimental value of the observed yield (Yobs) has been detected, with high values ranging from 0.56 to 0.75.